Production of protons, deuterons and tritons in argon-nucleus interactions at 3.2 A GeV - The BM@N collaboration; S. Afanasiev; G. Agakishiev; A. Aleksandrov; E. Aleksandrov; I. Aleksandrov; P. Alekseev; K. Alishina; V. Astakhov; T. Aushev; V. Azorskiy; V. Babkin; et al. (Journal of High Energy Physics)
Abstract Results of the BM@N experiment at the Nuclotron/NICA complex on the production of protons, deuterons and tritons in interactions of an argon beam of 3.2 A GeV with fixed targets of C, Al, Cu, Sn and Pb are presented. Transverse mass spectra, rapidity distributions and multiplicities of protons, deuterons and tritons are measured. The results are treated within a coalescence approach and compared with predictions of theoretical models and with other measurements.